استخدام تقنية الانحدار اللوجستي لتحديد أهم العوامل المؤثرة في تأخر سن الزواج في المملكة العربية السعودية - خليل، انتصار علي (جامعة الشارقة, 2016)
The present study attempts to investigate the factors that affect the delayed age of marriage, which is considered a social phenomenon rampant in Arab societies. The researcher uses a binary logistic regression model to identify the most important factors that lead to the spread of this phenomenon from the perspective of Umluj community in Saudi Arabia. To determine the variables that affect the phenomenon, information has been gathered from male and female married and unmarried people who are employees of the University College in Umluj (students and staff). The questionnaire consists of a collection of items that may affect the delayed age of marriage in the Arab societies. The questionnaire was distributed to a sample (intentional) composed of 100 males and 100 females. The number of questionnaires received was157 (82 males and 75 females). The researcher conducted an initial descriptive study to come out with initial indicators about the phenomenon. Then the binary logistic regression model was applied using two ways Enter and Stepwise procedures, to determine the most important factors that affect the delayed age of marriage. The study found that the most important factors that affect the delayed age of marriage were: parental loss or one of them (the boy or the girl) take the responsibility of rearing brothers, ambitious excess in partner specifications, estimating an individual family, the composition, friendship and mixing between the sexes across social media, and boast and brag about the requirements of marriage.
يتضمن هذا البحث دراسة العوامل المؤثرة في ظاهرة تأخر سن الزواج، كظاهرة اجتماعية متفشية في المجتمعات العربية. استخدم الباحث أسلوب الانحدار اللوجستي ثنائي الاستجابة لتحديد أهم العوامل المؤدية إلى تفشي هذه الظاهرة من وجهة نظر مجتمع مدينة أملج بالمملكة العربية السعودية. ولتحديد المتغيرات التي تؤثر في الظاهرة تم جمع معلومات من الذكور والإناث، المتزوجين وغير المتزوجين من منسوبي الكلية الجامعية بأملج (طلبة وموظفين)، حيث تم تصميم استبانة توضح مجموعة من العناصر التي قد تؤثر في تأخر سن الزواج في المجتمعات العربية، وزعت الاستبانة على عينة عمدية مكونة من 100 من الذكور، و100 من الإناث، عدد الاستبانات الراجعة 157 استمارة بواقع 82 ذكور و75 إناث. تم إجراء دراسة وصفية أولية للخروج بمؤشرات أولية عن الظاهرة ومن ثم تم تطبيق نموذج الانحدار اللوجستي ثنائي الاستجابة بطريقتي (Enter) و (Stepwise) لتحديد أهم العوامل المؤثرة في تأخر سن الزواج. كما تم اختبار جودة توفيق النموذج بالإضافة إلى اختبار الصدق والثبات لأداة البحث. توصلت الدراسة إلى أن من أهم العوامل التي تؤثر في تأخر سن الزواج: فقدان الوالدين أو أحدهما وتحمل الفتى أو الفتاة مسؤولية تربية الإخوة، والطموح الزائد في مواصفات الشريك، وتقدير الفرد للأسرة التي ينوي تكوينها، والصداقة والاختلاط بين الجنسين عبر مواقع التواصل الاجتماعي، والتفاخر والتباهي بمتطلبات الزواج.
Keywords: الإنحدار اللوجستي -- سن الزواج -- الظواهر الاجتماعية -- ظاهرة العنوسة -- المجتمعات العربية -- السعودية